Disinfection byproducts and their toxicity in wastewater effluents treated by the mixing oxidant of ClO2/Cl2. (1st October 2019) - Zhong, Yu; Gan, Wenhui; Du, Ye; Huang, Huang; Wu, Qianyuan; Xiang, YingYing; Shang, Chii; Yang, Xin
Abstract: Mixing oxidant of chlorine dioxide (ClO2 ) and chlorine (Cl2 ) often applied in water disinfection. Two secondary wastewater effluents at different ammonium-N levels (0.1 and 1.6 mg N L −1 ) were treated with the mixing oxidant (ClO2 /Cl2) to evaluate the formation of disinfection byproducts (DBPs) and the associated cytotoxicity of treated wastewaters. The total chlorine concentrations of ClO2 and Cl2 were maintained at 10 mg L −1 as Cl2 with varied mixing ratios of ClO2 to Cl2 . The formation of 37 halogenated DBPs, including nitrogenous, brominated and iodinated analogues, and 2 inorganic DBPs (chlorite and chlorate) was examined. The sum concentrations of the halogenated DBPs were reduced remarkably with decreasing Cl2 percentages, but each individual DBP group had distinct features. The regulated trihalomethanes reduced the most when ClO2 was present in chlorination, but decreasing Cl2 percentage from 70% to 30% was not quite effective to reduce the formation of iodinated trihalomethanes, haloacetic acids and haloacetontriles in low ammonium-N wastewater. The bromine and iodine substitution factors tend to increase with decreasing Cl2 percentages, indicating that destruction of DBP precursors by ClO2 favored bromine and iodine incorporation. Additionally, decreasing Cl2 percentages in the mixing oxidant (ClO2 /Cl2 ) was often accompanied with lower chlorate formation but higher chlorite formation. The toxicity of treated wastewaters was evaluated through two approaches: the calculated cytotoxicity based on the concentrations of detected DBPs and the experimental cytotoxicity using the Chinese hamster ovary (CHO) cells. The calculated cytotoxicity decreased with decreasing Cl2 percentages, with haloacetonitriles and haloacetaldehydes as predominate contributors. However, the experimental cytotoxicity tests showed that treatment of high ammonium-N wastewater with ClO2 /Cl2 exhibited considerable higher (> 3 times) cytotoxicity potency than using single disinfectant. Graphical abstract: Image 1 Highlights: DBP formation and cytotoxicity were evaluated in ClO2 /Cl2 treated wastewater. The formation of halogenated DBPs decreased with decreasing chlorine percentages. ClO2 presence reduced THMs the most, but not HAAs and HALs in low NH3 –N wastewater. Decreasing Cl2 percentages resulted in more bromine and iodine substitution in DBPs. High NH3 –N wastewater treated by ClO2 /Cl2 had significantly enhanced cytotoxicity.